خصائص نبویﷺ اور کلامِ امام احمد رضا خاں قادری: Unique Characteristics of the Prophet (SAW) and the poetry of Imam Ahmed Raza Khan Qadri - Dr Muhammad Sohail Shafiq (AL-IDRAK JOURNAL, 2022)
Allah Almighty has endowed His Messenger Muhammad (SAW) with innumerable attributes and perfections which are distinguished him from other Prophets.These characteristics are of two kinds: one is that which you have in comparison to other Prophets and Messengers (peace be upon them) such as: you are first in creation, being first in prophecy, being the last of the prophets, on the Day of Judgment, you will be promoted to the position of Maqam-e-Mahmood, you will be given the right of intercession (Shafa’at), you will be testified by the Prophets (peace be upon them) that they have conveyed the message of truth to their people. Second is that which were given in comparison to his Ummah, such as his legislative powers, the obligation of Tahajjud prayers, fasting, etc. These characteristics are mentioned in detail in the Holy Quran and Hadith. Like various aspects of the Prophet's biography, scholars and researchers have authored numerous books on this subject, both in prose and poetry. Imam Ahmad Raza Khan Qadri is also an important name among these scholars. He was a prominent religious scholar, jurist, author, Na’at poet and genius working personality of his time. The purpose of this article is to give a brief overview of the characteristics of the Prophet (peace and blessings of Allah be upon him) in the light of the poetry of Imam Ahmad Raza Qadri.